Paracetamol overdosing with 6500 mg single dose: Case report - Murthy Shiva N.; Kumar Anil H. (Srpsko lekarsko drustvo, 2022)
Introduction: Paracetamol is available as a fixed dose combination with many non-steroidal anti-inflammatory drugs (NSAIDs) such as Ibuprofen, Diclofenac, Mefenamic acid, Aceclofenac etc. On the other hand, it is also considered as the most common cause of overdosing and poisoning. Paracetamol can be purchased both by prescription or as an OTC medicine. Case report: This paper represents a case of a male, age 27, vegetarian, who does regular exercise, alcoholic, who self-overdosed with 6500 mg (~10 tablets of 650 mg each) of Paracetamol with suicidal intention. An attempt has been made to discuss the effects of Paracetamol on liver, kidney and other organs function through hematology, biochemistry, urine investigations done within 24 hours and day 7 after overdosing. Results of additional investigations such as liver function tests done on day 4 and day 5, X-ray chest, ultrasound scan of the abdomen and ECG done on day 1 were also included for discussion. Liver parameters were checked for presence of Drug Induced Liver Injury (DILI) using an algorithm published by Pineda S L et al. Conclusion: Results of this case analysis suggested the presence of mild DILI with a single dose of 6500 mg Paracetamol. We recommend further studies using algorithm of Pineda S L et al to assess the minimum doses that are expected to cause clinically significant DILI and recommend policies to drug regulators of the country to restrict the maximum number of doses that can be sold to the general public on OTC basis.